Control of graft-versus-host disease and graft rejection by T cell depletion of donor and recipient with Campath-1 antibodies. Results of matched sibling transplants for malignant diseases. - Hale, G; Waldmann, H (1994)
Campath-1 (CDw52) antibodies (IgM and IgG2b) have been used in vitro and in vivo for control of GVHD and prevention of rejection following bone marrow transplantation. Results of 951 patients with malignant disease transplanted from HLA-matched siblings are reported. Both Campath-1M and Campath-1G are shown to be effective when used in vitro for prevention of graft-versus-host disease (GVHD). Graft failure was reduced by addition of cyclosporin A (CsA) post-transplant and possibly also by total lymphoid irradiation (TLI) pre-transplant. However, treatment of the recipient with Campath-1G to deplete residual lymphocytes was more effective, reducing the incidence of graft failure from 21% to 9% (in the absence of CsA). GVHD was virtually eliminated and leukaemia-free survival was improved. However, the risk of relapse was increased by T cell depletion, certainly in CML and to a lesser extent in AML. Addition of donor T cells to the depleted bone marrow or early post-transplant restored the risks of GVHD, graft failure and relapse to much the same as without T cell depletion. One problem associated with the use of Campath-1G in vivo was a significant delay (by up to 7 days) in neutrophil engraftment. This was unlikely to be caused by toxicity to progenitor cells and we argue that small numbers of lymphocytes may be required to assist early engraftment, possibly by cytokine production. If this problem can be overcome, T cell depletion of donor and recipient may be a good alternative to conventional GVHD prophylaxis for matched sibling transplants, resulting in a superior quality of life for the survivors. It is also likely to be particularly beneficial in transplants for non-malignant diseases and transplants from unrelated donors.